Indoor Air Quality (IAQ) and Related Risk Factors for Sick Building Syndrome (SBS) at the Office and Home: A Systematic Review. Issue 1 (1st February 2023) - Aziz, Norsaffarina; Adman, Mohammad Adam; Suhaimi, Nurud Suria; Misbari, Syarifuddin; Alias, Ahmad Rizal; Aziz, Azrina Abd; Lee, Lim Fang; Khan, Md Mobarak Hossain
Abstract: The comfort and productivity of workers may be affected differently by the indoor air quality (IAQ) and related risk factors at the office and at home. Sick Building Syndrome (SBS) is one of the health issues usually faced by workers. SBS is generally associated with the time spent in a building, IAQ, and other related risk factors. The study reviewed papers published in journal articles and conferences regarding IAQ, environmental risk factors and SBS in the last ten years. The review employed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) 2020 items from two significant databases, Scopus and Web of Science. The review steps involved identification, screening, eligibility, data extraction and analysis. The study found that air quality in a building significantly influences work productivity and may contribute to SBS. Findings show that SBS symptoms are linked to various personal characteristics, sociodemographic, working environment and IAQ factors. The physical contaminants, chemical contaminants and ventilation rate have established relations with SBS symptoms. These findings can help to form interventions aiming to improve IAQ and the productivity of occupants.